Organizações e a construção social do ambiente legal do controle de registro eletrônico de ponto no Brasil - Santiago, Josiane da Silva Oliveira (2016)
This work aims to analyse how the relationship between legal rules and organizational practices of working time control was manifested in the social construction process of the legal environment of Point Electronic Registration in Brazil, regulated by Decree nº 1.510/2009, the period 2009-2015. The research is based on organizational institutionalism in perspective that considers the constituent aspects of the legal environment in which the social actor Interact in the construction of meanings around the legal rule seeking compliance with the existing rules. In this approach, the research provides a historical background on the working day control practices in Brazil, the main landmarks of the legal change, as well as organizational and media responses. The research is qualitative and research strategy was the case study exploratory and descriptive character and perspective time with collecting retrospective sectional data. The data were collected from documents, interviews and questionnaire. It was identified that the Decree nº 1.510/2009 appeared unilaterally bringing different specifications of electronic means of working time control used until that moment, and how enforcement mechanism to organizations. In this context, some relevant aspects were identified: (i) imitation – legal change is anchored in similar practice adopted in other government agency; (ii) expansion of the scope of the legal rule - the active participation of stakeholders impacted in coupling the legal rule to the existing organizational practices; from the publication of Decree nº. 373/2011 organizations could use alternative means of electronic point record; (iii) transfer of responsibility for analysis of compliance - the union became responsible for certifying the conformity of alternative electronic means; (iv) legal relegation - INMETRO became responsible for defining the specifications of electronic registration point equipment; (v) reconstruction of legality: from Decree nº. 101/2012 MTE delegated to the INMETRO responsibility not only the definition of technical specifications as well as for monitoring the compliance of organizations to these standards; (vi) relativity of silencing debate: the perception of stakeholders on the acceptance of legal change in social practice is related to the interests of stakeholders. Regarding the dissemination of the legal rule, it was evident the legal validity of Decree nº 1.510 / 2009 from the judgments analyzed, while in relation to social validity did not identify themselves adherence to the organizational sphere. In conclusion, it was evident the recursion between the law in books and law in practice in a sphere in which social actors have actively participated in implementation of the legal rule and the social construction of the legal environment. Still, the consttuction of legality was identified not only about the legal rule content, but also in relation to the legislator social actor and the legal device used for implementation of the legal rule.